Enhancement of Activity and Thermostability of Keratinase From Pseudomonas aeruginosa CCTCC AB2013184 by Directed Evolution With Noncanonical Amino Acids - Pan, Xianchao; Yang, Jian; Xie, Peijuan; Zhang, Jing; Ke, Famin; Guo, Xiurong; Liang, Manyu; Liu, Li; Wang, Qin; Gao, Xiaowei (Frontiers in Bioengineering and Biotechnology, 2021)
A keratinase from Pseudomonas aeruginosa (KerPA), which belongs to the M4 family of metallopeptidases, was characterised in this study. This enzyme was engineered with non-canonical amino acids (ncAAs) using genetic code expansion. Several variants with enhanced activity and thermostability were identified and the most prominent, Y21pBpF/Y70pBpF/Y114pBpF, showed an increase in enzyme activity and half-life of approximately 1.3-fold and 8.2-fold, respectively. Considering that keratinases usually require reducing agents to efficiently degrade keratin, the Y21pBpF/Y70pBpF/Y114pBpF variant with enhanced activity and stability under reducing conditions may have great significance for practical applications. Molecular dynamics (MD) was performed to identify the potential mechanisms underlying these improvements. The results showed that mutation with pBpF at specific sites of the enzyme could fill voids, form new interactions, and reshape the local structure of the active site of the enzyme.